A10.15 LASP-1 modifies ECM-synovial fibroblast interactions in a mouse model of ra. (24th February 2016) - Beckmann, D; Hillen, J; Heitzmann, M; Hansen, U; Kiener, HP; Chew, CS; Butz, S; Vestweber, D; Pavenstädt, H; Galla, HJ; Pap, T; Korb-Pap, A
Abstract : Background and objectives: The LIM-and-SH3-domain-protein-1 (Lasp-1) is an actin-associated protein and is localised at focal adhesion sites where it is involved in organisation of actin polymerization and focal adhesion turnover prozesses. We investigated its role in regulating synovial fibroblast (SF) interaction with components of the extracellular matrix (ECM) and in establishing cell-cell contacts during RA. Materials and methods: Lasp-1 expression was analysed in tissue from RA patients and in the hind paws of arthritic hTNFtg mice by Western blot, immunofluorescence and immunohistochemistry. Furthermore, Lasp-1 -/- mice were interbred with hTNFtg mice and offsprings were analysed for the progression of joint destruction by clinical evaluation and histopathology. Migration characteristics of SF derived from wild type (wt), Lasp-1 -/-, hTNFtg and Lasp1 -/- /hTNFtg mice were analysed in a modified scratch assay and by live cell imaging. Cell-matrix interactions and cell-cell contacts of isolated SF from all different genotypes were investigated using fibronectin coating in an electrical cell/substrate impedance sensing assay (ECIS). Additionally, we used an in vitro three-dimensional organ culture system for functional analyes. Results: Lasp-1 expression levels were increased in human RA tissue and hTNFtg mice in comparison to healthy controls. Evaluation of Lasp-1 -/- /hTNFtg mice revealed milder arthritis score compared to hTNFtg mice, which was confirmed by immunohistochemistry. Results of the scratch assays demonstrated a significantly reduced migration rate of Lasp-1 -/- SF (-43, 7% vs wt SF) and Lasp-1 -/- /hTNFtg SF (-69, 11% vs hTNFtg SF). Furthermore, live cell imaging studies demonstrated striking differences in the migration velocity and in migration edge formation of Lasp-1 -/- /hTNFtg SF compared to hTNFtg SF. ECIS analysis demonstrated an increased cell-cell contact formation in Lasp1 -/- compared to wt SF (+22% versus wt SF) and prolonged cell-cell interaction remodelling of Lasp-1 -/- /hTNFtg SF in comparison to hTNFtg SF. Histological analysis of 3D matrices showed that Lasp-1 deletion in the hTNFtg background resulted in an organised cellular lining layer at the interface between the matrix and fluid phases comparable with wild type SF. In contrast, hTNFtg SF formed unorganised cellular condensations with no synovial architecture evident. Conclusion: Lasp-1 regulates the migratory behaviour of synovial fibroblasts in rheumatoid arthritis by controlling the dynamics of cell-matrix and cell-cell contacts.